Nivel de ansiedad de los niños de 5 a 8 años de edad en la consulta odontológica con o sin manejo de técnicas de distracción - Torres Jaramillo, Karina Natalhie (2019)
Patients who experience fear in the dental office make it difficult to carry out clinical activities and in certain cases do not continue attending appointments, which prevents the success of the treatment. The objective of this research is to determine the level of anxiety of children aged 5 to 8 years during dental consultations, with or without handling of distraction techniques. The study is quantitative, cross-sectional and observational. The population studied included a group of 20 children of both genders, from 5 to 8 years old, who attended both public and private dental clinics. The level of anxiety was evaluated through two instruments: a Facial Expression Scale before treatment and the Venham graphic test after treatment. The results obtained showed that 40% of the children treated at the dentistry clinic of the University Hospital of Motupe presented moderate levels of anxiety and fear before treatment, while after the dental treatment, 60% presented moderate anxiety. In the private practice, 60% of children showed mild anxiety, while after the treatment 80% of the children presented without anxiety. We conclude that anxiety and fear diminish if techniques of audiovisual distraction and music therapy are used. Keywords: Fear, treatment, behavior, expression, values.